Capacities and Constraints in Livelihood Adaptation to Climate Change in Marine Fisheries of Odisha - Sambit Priyadarshi; S.N. Ojha; Arpita Sharma (Journal of Indian Fisheries Association, 2020)
Climate change is expected to have the worst eﬀect on the natural resource-dependent fishing communities in various ways. Being exposed to 260 cyclonic events during the last century, Odisha is one of the most vulnerable states to climate change. Based on the above facts, a study was conducted in the state of Odisha to assess the adaptive capacity of the marine fishers and to diagnose the constraints faced by them. Information was collected from 120 marine fisher households of Balasore and Ganjam district of Odisha by employing a multi-stage sampling method. The interview schedule, along with Focus Group Discussion, Key Informants Interview, were used to elicit the required information. Further, the data were analyzed through descriptive analysis to draw meaningful interpretation. The adaptive capacity of the marine fishers was also found to be lower, contributed by low educational level (3.29±2.58 years of schooling, income inequality ( Balasore COV= 1 . 08 , Ganjam COV= 0 . 52 ) , and lack of alternative/subsidiary occupational avenues. The adaptation was found to be constrained by higher cost of operations due to the increasing fuel cost and reduced fish catches, sub-optimal market infrastructure, borrowing from non-institutional sources at a higher interest rate, higher cost of fishing technologies, lower educational level, consumption of low-quality fish, seasonal unemployment, lack of skills other than fisheries. The present study recommends skill development and financial inclusion campaign along with various short term and long term corrective policy measures to enhance the adaptive capacity of fishers.